Kampus dan Republik: Merawat Republik, Mengaktifkan Akal Sehat? - Siti Nurhayati; Masduki Asbari; Umul Musfiroh (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to determine the function of campuses and republican ideas. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to an oral narrative from the Bosowa University YouTube channel entitled "campus and republic" presented by academic Roky Gerung. The results of this study explain that the function of the campus is to oversee public policy and this can take place in the lecture hall or on the highway. The campus has a very strategic position to produce sensible people with high intellectual qualities. We seem to live in two Republics: Republic of Fear and the Republic of Hope. Our common sense certainly wants the realization of the Republic of Hope, thoroughly and in the shortest possible time. But it seems that the political authorities prefer to maintain the Republic of Fear, because that is where election statistics are at stake.